Micromagnetic modeling of magnetic anisotropy in textured thin-film media - Zhao, Yang (2011)
Existing micromagnetic models, based on single domain grains that individually follow coherent rotation during reversal, have been utilized to study the effect of various texture-induced microstructures on the hysteretic behavior of Co-alloy thin films with circumferentially textured substrates. The roles of preferential orientation of Co c axes, grain elongation, and segregation, as well as possible short-range intergranular coupling, have been examined in an effort to understand the origins of widely observed magnetic anisotropy in these media. Preferential c-axis distribution along the track direction yields reasonable remanences and coercivities for both circumferential and radial loops, but the observed loop closure remains unaccounted for by c-axis distribution alone. Closely packed arrays of elongated grains maintain relative isotropy in terms of magnetostatic interactions, while voids along texture lines contribute to the magnetostatic anisotropy of the film. The limitations of the model are also discussed.